1982
DOI: 10.1152/ajpheart.1982.242.5.h875
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of local myocardial stress

Abstract: Two formulas are presented for estimating local average circumferential stress in the left ventricle from the cavity pressure and various quantities, available from the angiogram, which characterize the size and shape of the cavity and ventricular wall. The advantages of these formulas are as follows: 1) they are based on thick-wall shell theory; 2) they are intended for application at positions in the ventricular wall other than the base; and 3) they are based on a more general representation of ventricular g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
39
0

Year Published

1988
1988
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 0 publications
4
39
0
Order By: Relevance
“…8 Other indirect evidence of increased regional wall stress is derived from studies assessing wall curvature on a regional basis in the chronic postinfarct LV. 25,26 Regional thickness and blood pressure were similar between treatment groups in this study, but EDV and ESV (and hence ventricular radii) are reduced with CT compared with controls, AT 1 blockade, and sACEI. Thus, wall stress must be lower by the Laplace relationship and could contribute to improved EF and adjacent %S.…”
Section: Discussionsupporting
confidence: 50%
“…8 Other indirect evidence of increased regional wall stress is derived from studies assessing wall curvature on a regional basis in the chronic postinfarct LV. 25,26 Regional thickness and blood pressure were similar between treatment groups in this study, but EDV and ESV (and hence ventricular radii) are reduced with CT compared with controls, AT 1 blockade, and sACEI. Thus, wall stress must be lower by the Laplace relationship and could contribute to improved EF and adjacent %S.…”
Section: Discussionsupporting
confidence: 50%
“…16 In addition, in a regionally ischemic heart, changes in regional radius of curvature, which were not measured in the present study, would occur in the ischemic region, and hence might affect wall tension of this region . 31 However, our previous study22 has shown that the global integral of regional work determined by the T-A loop method closely agrees with measured total left ventricular work both before and after coronary occlusion, suggesting that the influence of changes in regional wall tension on the measurement of regional work during regional ischemia is very small.…”
Section: Discussionmentioning
confidence: 70%
“…LV volumes were indexed by the body surface area (LVEDVI and LVESVI, respectively). Local ESS was calculated on the basis of the Janz equation 1 12 ; ESSϭPϫ⌬Ac/⌬Aw, where P is LV end-systolic pressure, and ⌬Ac and ⌬Aw are local cross-sectional area of the LV cavity and local cross-sectional area of the LV wall at end-systole, respectively. In this study, LV end-systolic pressure estimate was obtained with a following equation: Pϭ0.98ϫ(systolic blood pressureϩ2ϫdiastolic blood pressure)/3ϩ11 mm Hg.…”
Section: Mdct Image Analysismentioning
confidence: 99%